1999
DOI: 10.1023/a:1007541317104
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The pattern of faecal excretion of Vibrio cholerae was studied over a duration of eight months among 13 cholera convalescents by two-weekly surveillance cultures. Stools and rectal swabs were cultured on Thiosulphate citrate bile salts sucrose (TCBS) agar for the recovery of vibrio pathogens. Clinical phase and convalescent phase V. cholerae strains were compared for antibiogram profiles. The population of vibrios recovered from faecal inocula was usually scanty (<10(3) vibrios/g). All clinical isolates except… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Furthermore, considering that the V . cholerae load in stools from convalescent and long-term carriers is reportedly in the range of 10 2 to 10 3 CFU/g [ 43 , 44 ] the method is also valuable for the bacterium detection in these samples.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, considering that the V . cholerae load in stools from convalescent and long-term carriers is reportedly in the range of 10 2 to 10 3 CFU/g [ 43 , 44 ] the method is also valuable for the bacterium detection in these samples.…”
Section: Resultsmentioning
confidence: 99%
“…Mathematical modeling suggests that an association between HIV and cholera may also exist in the endemic setting [ 15 ]. Beyond this, evidence is limited to several small case series [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study from Nigeria followed 13 cholera convalescent patients with twice weekly stool cultures and rectal swabs and showed that 69% of the convalescents had positive cholera faecal cultures for periods ranging from two weeks to more than seven months [45]. However, as in all endemic-region studies, reinfection rather than long-term shedding could not be discounted.…”
Section: Choleramentioning
confidence: 99%